Methodology of recreation in the structure of the educational space - Viacheslav Zaytzev; Sergii Iermakov; Magdalena Hagner- Derengowska (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. The aim of the study is to present the methodological aspects of health, healthy lifestyle and recreation of students in higher educational institutions.